The Effect of Training Self-Management, Attention Behaviors, and Motivational Behaviors on Reducing Anxiety and Stress of Selecting a University Major in Students - Askarshahi, Neda; Ghanbari, Negar; Shabannejad Chenani, Elham; Toloue Asghari, Mahlagha; Almasian, Hanie (International Journal of Education and Cognitive Sciences, 2022)
Purpose: Choosing to pursue further education and selecting a specific field of study after completing high school is a crucial decision that can bring about a significant amount of stress and anxiety for individuals. The main objective of this study is to explore how training self-management techniques for attention and motivation can help reduce the anxiety and stress associated with choosing a university major among students. Methods and Materials: The purpose of the current study was to apply semi-experimental methods, including pre-test, post-test, follow-up, control group, and two experimental groups. The research focused on male and female students majoring in mathematics, experimental sciences, and humanities in Tehran in 2023. The initial sample size was 37 individuals chosen through purposive sampling. Educational programs were conducted for a total of four sessions in one week, with each session lasting 45 minutes. The study utilized Beck Anxiety Inventory (BAI) and Perceived Stress Questionnaire (PSQ) as measurement tools. Data analysis was conducted with SPSS version 27 and JASP version 0.18.1.0 software, utilizing the Kruskal-Wallis H test, repeated measure ANCOVA, and Bonferroni's Post Hoc Test at a P-value of 0.05.  Findings: During the follow-up and post-test phases of the study, there was a significant difference in stress levels between the group that focused on self-management of attentional behaviors and the control group (P